2019
DOI: 10.1111/jfbc.13077
|View full text |Cite
|
Sign up to set email alerts
|

Soluble melanins of the Randia echinocarpa fruit – Structural characteristics and toxicity

Abstract: The water-soluble melanins (SM) of Randia echinocarpa fruit possess interesting biological activities and have been scarcely characterized. In this study, SM were obtained at boiling (SMBT) and room (SMRT) temperatures and characterized by UV-Vis, IR, thermogravimetric analysis, and GC-MS of the hydrolysis products of the SM; besides, the solid-state 13 C NMR, elemental analysis, and acute and sub-acute toxicity of the SMBT were determined. SMBT and SMRT contain organic acids and carbohydrates and their spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Melanoidins of non-fermentation origin typical for the original seed coats, fruit shells, or root epidermis from Castanea mollissima [ 65 ], Echinacea purpurea [ 66 ], Nigella sativa [ 67 ], Randia echinocarpa [ 68 ], Sesamum indicum [ 69 ], and Helianthus anuus [ 70 ] showed slightly different values. The value of the atomic ratio H/C (0.89) indicated the predominance of aromatic fragments in the EAM structure, and the value of O/C (0.48) showed the presence of oxygen functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Melanoidins of non-fermentation origin typical for the original seed coats, fruit shells, or root epidermis from Castanea mollissima [ 65 ], Echinacea purpurea [ 66 ], Nigella sativa [ 67 ], Randia echinocarpa [ 68 ], Sesamum indicum [ 69 ], and Helianthus anuus [ 70 ] showed slightly different values. The value of the atomic ratio H/C (0.89) indicated the predominance of aromatic fragments in the EAM structure, and the value of O/C (0.48) showed the presence of oxygen functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, R. echinocarpa extracts have antioxidant, immunomodulatory, and antimutagenic activities that have been considered essential to treat various diseases, including malaria and cancer (Munialo et al 2019), and support the traditional uses of the species. Supporting the potential of R. echinocarpa as a source of phytotherapeutic compounds, toxicity assays in mice showed that soluble melanins from fruit were innocuous, and treated mice showed normal behavior, weight, and healthy organs (Gil-Avilés et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…No approved prophylaxis or therapy exists for these toxicities (2) . Considering the high toxicity of the radiation treatment to the gastrointestinal tract, studies revealing natural radio protectors that regulate the gastrointestinal tract response to injury following irradiation are extremely beneficial (3)(4)(5) . The genus Eucalyptus L'Heritier comprises about 300 species contains volatile essential oil in their leaves (6) .…”
Section: Introductionmentioning
confidence: 99%